Use of probiotic Bacillus megaterium NCH 55 for treatment of subclinical mastitis in cows – preliminary study - Oksana Shkromada; Alina Pikhtirova; Ewa Pecka-Kiełb; Oleksandr Skliar; Yurii Musiienko (Macedonian Veterinary Review, 2022)
The development and implementation of new and safe means of treating subclinical mastitis (SM) in the production process remains a pressing problem. Our study aimed to investigate the therapeutic effect of the Bacillus megaterium NCH 55 strain on cow SM. All animals with signs of SM were fed with a basic diet with probiotic’s addition of 15 g/per day. The experiment was conveyed in 30 consecutive days. Milk and blood were collected on the 7th, 15th, and 30th day of the experiment. Daily milk yield was increased by 32.2% and somatic cell count was decreased from 290.00±32.12 to 96.80±39.03 ths/cm3. A decrease in inflammation was indicated by a decrease in POM370 (by 2.2 times) and POM430 (by 2.8 times). No significant changes in the blood serum indices of cows were observed. A probiotic’s positive effect has been established on the treatment of SM. The probiotic B. megaterium NСH 55 can be considered as an alternative to antibiotics and other chemotherapeutic drugs for treating SM in cows.